Development and properties of soybean spreads - Che Man, Yaakob; Yee, Yeong Nyet (Wiley-Blackwell Publishing, 1996)
Soybean spreads were developed by concentrating soymilk with the addition of sugar, sorbitol, sodium citrate, carrageenan and refined bleached and deodorized (RBD) palm olein. Soymilk was prepared by 3 extraction methods: soaking in water (control), blanching at 85C with sodium bicarbonate (NaHCO3) solution and acid treatment using HCl. Three different types of soybean spreads were developed using these soymilks. The spreads were evaluated for their proximate composition, pH, water activity (Aw), color, spreadability, sensory characteristics and storage stability. Sensory and spreadability results showed that soybean spread from blanched and alkali-treated soymilk was most acceptable and showed better spreadability than the others. It was more yellowish in color, possessed lower Aw and firmer texture. The shelf-life of all three types of spreads at refrigerated temperature were at least 30 days.